2014
DOI: 10.1021/es5006972
|View full text |Cite|
|
Sign up to set email alerts
|

Hydroxylated, Methoxylated, and Parent Polybrominated Diphenyl Ethers (PBDEs) in the Inland Environment, Korea, and Potential OH- and MeO-BDE Source

Abstract: The concentrations, congener profiles, and phase-specific distribution profiles of 27 polybrominated diphenyl ethers and 10 hydroxylated and 18 methoxylated brominated diphenyl ethers (OH- and MeO-BDEs; later called structural analogues of PBDEs) were determined in surface soil, water, air, and vegetation from the southeastern city of Busan, Korea for 2010-2011. The total PBDE concentrations were 0.18-7.7 ng/g in soil, 6.3-87 pg/L [corrected] in water, 5.3-16 pg/m(3) in air, and 0.06-0.22 ng/g in vegetation. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Based on the knowledge of their adverse effects on the environment and human health, some PBDEs have been included on the Stockholm Convention list of priority persistent organic pollutants, and some technical products have been banned or voluntarily withdrawn from use in some regions of the world (California State Assembly, 2003;Cox and Efthymiou, 2003). However, owing to their high volume production, long-term use, and lipophilic and persistent properties, PBDEs are still frequently detected in various environmental media (Kim et al, 2014;Newton et al, 2015) and biotic samples (Shang et al, 2013;Wang et al, 2014;Zhu et al, 2009) in the environment. Therefore, there is considerable concern about their behaviors and fates in the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the knowledge of their adverse effects on the environment and human health, some PBDEs have been included on the Stockholm Convention list of priority persistent organic pollutants, and some technical products have been banned or voluntarily withdrawn from use in some regions of the world (California State Assembly, 2003;Cox and Efthymiou, 2003). However, owing to their high volume production, long-term use, and lipophilic and persistent properties, PBDEs are still frequently detected in various environmental media (Kim et al, 2014;Newton et al, 2015) and biotic samples (Shang et al, 2013;Wang et al, 2014;Zhu et al, 2009) in the environment. Therefore, there is considerable concern about their behaviors and fates in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a hydroponic experiment was conducted although it cannot entirely exclude the influences from root-associated microbes. BDE-47 is frequently detected in PBDE-contaminated soils and accumulated in plants at relatively high concentrations (Kim et al, 2014;Sun et al, 2013b). So, BDE-47 and its hydroxylated and methoxylated analogs (6-OH-BDE-47 and 6-MeO-BDE-47) were selected as the target compounds, and their kinetic uptake by roots and acropetal translocation in maize were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,10 Our findings suggest that the transformation of BPs by sunlight irradiation may contribute to the production of OH-PBDEs and di-OH-PBBs in aqueous environments. Given that phenoxyl radicals may also react with dissolved organic matter (DOM) or other constituents in natural water, further studies are needed to determine to which extent the phototransformation of BP contributes to the contamination of surface waters with OH-PBDEs.…”
Section: Resultsmentioning
confidence: 71%
“…There is increasing evidence that OH-PBDEs are ubiquitous in biotic and abiotic environments. 1,2 These pollutants have been observed in abiotic compartments such as rain, snow and wastewater influent and effluent. 25 Recent studies report that the sum of OH-PBDEs (ΣOH-PBDEs) are 15–170 pg m −2 d −1 in rain and 3.5–190 pg m −2 d −1 in snow 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In marine sediments, the mean concentration of 6-OH-BDE 47 was 22 ± 2.3 pg/g dw in Liaodong Bay, China [ 27 ] and levels ranged from 11.4 to 128 pg/g dw in the East China Sea [ 28 ]. In fresh waters, observed OH-BDEs levels ranged from 34 − 390 pg/L in South Korean rivers [ 29 ] and 2.2–70 pg/L in Lake Ontario and the Detroit River [ 8 ]. A recent study reported ΣOH-BDEs fluxes of 15 to 170 pg/m 2 /day in rain and 3.5 to 190 pg/m 2 /day in snow [ 8 ].…”
Section: Introductionmentioning
confidence: 99%